Early Synapse-Specific Alterations of Photoreceptor Mitochondria in the EAE Mouse Model of Multiple Sclerosis - Dalia R. Ibrahim; Karin Schwarz; Shweta Suiwal; Sofia Maragkou; Frank Schmitz (Cells, 2025)
Multiple sclerosis (MS) is an inflammatory autoimmune disease of the central nervous system (CNS) linked to many neurological disabilities. The visual system is frequently impaired in MS. In previous studies, we observed early malfunctions of rod photoreceptor ribbon synapses in the EAE mouse model of MS that included alterations in synaptic vesicle cycling and disturbances of presynaptic Ca2+ homeostasis. Since these presynaptic events are highly energy-demanding, we analyzed whether synaptic mitochondria, which play a major role in synaptic energy metabolism, might be involved at that early stage. Rod photoreceptor presynaptic terminals contain a single large mitochondrion next to the synaptic ribbon. In the present study, we analyzed the expression of functionally relevant mitochondrial proteins (MIC60, ATP5B, COX1, PINK1, DRP1) by high-resolution qualitative and quantitative immunofluorescence microscopy, immunogold electron microscopy and quantitative Western blot experiments. We observed a decreased expression of many functionally relevant proteins in the synaptic mitochondria of EAE photoreceptors at an early stage, suggesting that early mitochondrial dysfunctions play an important role in the early synapse pathology. Interestingly, mitochondria in presynaptic photoreceptor terminals were strongly compromised in early EAE, whereas extra-synaptic mitochondria in photoreceptor inner segments remained unchanged, demonstrating a functional heterogeneity of photoreceptor mitochondria.